Reduced systolic wave generation and increased peripheral wave reflection in chronic heart failure - Curtis, Stephanie L; Zambanini, Andrew; Mayet, Jamil; McG Thom, Simon A; Foale, Rodney; Parker, Kim H; Hughes, Alun D (American journal of physiology. Heart and circulatory physiology, 2007)
1 International Centre for Circulatory Health, and 2 Department of Bioengineering, Faculty of Engineering, Saint Mary's Hospital and Imperial College, London, United Kingdom Submitted 6 October 2006 ; accepted in final form 23 March 2007 In human heart failure the role of wave generation by the ventricle and wave reflection by the vasculature is contentious. The aim of this study was to compare wave generation and reflection in normal subjects with patients with stable compensated heart failure. Twenty-nine normal subjects and 67 patients with heart failure (New York Heart Association class II or III) were studied by noninvasive techniques applied to the common carotid artery. Data were analyzed by wave intensity analysis to determine the nature and direction of waves during the cardiac cycle. The energy carried by an early systolic forward compression wave (S wave) generated by the left ventricle and responsible for acceleration of flow in systole was significantly reduced in subjects with heart failure ( P < 0.001), and the timing of the peak of this wave was delayed. In contrast, reflection of this wave was increased in subjects with heart failure ( P < 0.001), but the timing of reflections with respect to the S wave was unchanged. The energy of an expansion wave generated by the heart in protodiastole was unaffected by heart failure. The carotid artery wave speed and the augmentation index did not significantly differ between subjects with heart failure compared with normal individuals. The ability of the left ventricle to generate a forward compression wave is markedly impaired in heart failure. Increased wave reflection serves to maintain systolic blood pressure but also places an additional load on cardiac function in heart failure. cardiac function; blood pressure Address for reprint requests and other correspondence: A. D. Hughes, Clinical Pharmacology, National Heart and Lung Div., Faculty of Medicine, Imperial College London, QEQM Wing, St. Mary's Hospital, S. Wharf Rd., London W2 1NY, UK (e-mail: a.hughesatimperial.ac.uk )